Experimental study on pressure loss and collection efficiency of drift eliminators. (25th February 2019) - Ruiz, J.; Cutillas, C.G.; Kaiser, A.S.; Zamora, B.; Sadafi, H.; Lucas, M.
Highlights: Six different types of commercial drift eliminators have been fully characterized. Dimensionless correlations for the relevant parameters have been developed. Good agreement of the predicted results with the experimental measurements is found. An eliminator selection criterion is proposed based on dimensionless parameters. Abstract: Drift eliminators play a major role in cooling tower operation. They are designed to reduce the discharge aerosols in their exhaust air stream to a minimum since inhaled airborne particles can cause the well-known Legionnaires disease. However, the pressure drop induced into the air stream increases the power consumption of the system. Accordingly, the design and selection of these elements should be a trade-off between the pressure drop and the collection efficiency. In this paper, six commercial drift eliminators (vane, wire mesh, and honeycomb-type) have been characterized in terms of pressure drop and collection efficiency with the aim of providing reliable information that can be used in drift eliminator design and selection. Fifty-three experiments were conducted regarding the pressure drop and collection efficiency characterization of the eliminators. Generally speaking, for the same type of eliminators the higher the pressure drop, the more efficient it is. Concerning typologies, wire-mesh eliminators perform better than the rest in terms of both pressure drop and collection efficiency. Dimensionless correlations for the pressure drop coefficient and the collection efficiency have been developed for the tested eliminators, showing a good agreement with the experimental results. A selection criterion has been proposed based on the dimensionless parameters that govern the problem and the experimental data of power consumption. It is based on determining the power consumed by the fans of the tower by setting a limit of collection efficiency and the droplet distribution characteristics at the cooling tower outlet area.